Thermal Enhancement for Paraffinic Thermal Energy Storage by Adding Volcanic Ash - Dwi Chandra Adhitya; Dwi Rahmalina; Ismail Ismail; Muhammad Nurtanto; Hamid Abdillah (Universitas Sultan Ageng Tirtayasa, 2021)
Thermal energy storage has a good opportunity to be applied in engineering field, especially for low temperature application like automotive thermal management system. Paraffinic is a better option and considered as a good phase change material with main advantages like economically feasible, non-corrosive and safe. The main drawbacks of paraffinic system are low thermal conductivity and supercooling effect. The effort to improve the performance for paraffinic system is by g sensible material. Considering the spread of volcano in Indonesia, it can be used as sensible material for paraffinic system. The aim of the research is to examine the volcanic ash characteristic and the effect of sand addition on the paraffinic system. a standardized approach for sand examination is done and the effect of the hybrid PCM (90% paraffin and 10% volcanic ash mass ratio) are studied. The overall performance of hybrid PCM is better than pure paraffin where the vapor point of hybrid PCM is increased and there is no supercooling phenomenon observed.